Incidence of brown rot blossom blight caused by Monilinia laxa in organic sour cherry production in Hungary - Holb, I. J. (International Journal of Horticultural Science, 2006)
Brown rot blossom blight incidence was evaluated on two sour cherry cultivars (Kántorjánosi, Újfehértói fürtös) in an organic sour cherry orchard in Hungary in 2003 and 2004. Trees were grown according to the organic fruit production guidelines. Blossom blight incidence was similar in both cultivars in both years. In 2003, blossom blight incidences were low even in the untreated plots (less than 15 %). In 2004, brown rot blossom blight incidence reached almost 30 % in the untreated plots. Blossom blight incidence was significantly lower in the conventionally treated plots in both cultivars.